Handbook of Community Psychiatry - McQuistion, Hunter L.; Sowers, Wesley E.; Ranz, Jules M.; Feldman, Jacqueline Maus.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Recent years have seen the exponential growth of behavioral health services and technologies, with an expanding public behavioral health picture to match. In community psychiatry especially, person-centered competencies and issues continue to gain in prominence. The Handbook of Community Psychiatry reflects the rapid changes in the field, providing basic and specialized information in areas such as epidemiology, person-centered planning and care, innovations in practice, and treatment of special populations. Organized for maximum comprehension and retention, the text is packed with helpful visuals and technological links. The Handbook: Defines community psychiatry, reviews the history of the field, and expands on the guiding principles underlying practice. Devotes separate chapters to the major clinical competencies. Details evidence-based interventions and emerging models of treatment. Addresses the future of the field with chapters on systems and administrative issues, and updates on workforce and professional education and development. Features useful tables, figures, illustrations, and callout boxes throughout the text. Has capacity for software and internet formatting, including CD access, Kindle, and handheld applications. Coverage this comprehensive and practical makes the Handbook of Community Psychiatry indispensable to psychiatrists at all stages of their careers, as well as educators, students, trainees, and administrators in psychiatry and community behavioral health. Given the multidisciplinary nature of behavioral health services, the Handbook is an invaluable reference for psychiatric nurses, nurse practitioners, and physician assistants; social workers; community psychologists; counselors, and case managers.
Introduction: What is Community Psychiatry? -- Background: Community Psychiatry and History -- Basic Psychiatric Epidemiology -- Financing -- Advocacy: Community Organizing and Politics -- Recovery and Person-centered Care -- Context-specific Clinical Assessment -- Team-based Treatment -- Family Therapy in Public Sector Settings -- Motivational Interviewing -- Group Modalities/techniques -- Psychiatric Rehabilitation -- Case Management -- Physical Wellness -- Working with Peers -- Cultural Competence -- Assertive Community Treatment -- Family Psychoeducation -- Co-occuring Chemical Dependency and Mental Illnesses -- Supported Employment -- Illness Self-management and Recovery -- Psychopharmacology and its Adherence -- Trauma-based interventions -- Cognitive Therapy of Schizophrenia -- Clubhouse Models -- Supported Housing Models -- Telepsychiatry -- Integrated Primary and Mental Health Care -- Innovative Acute Care Models: Mobile, Emergency, Crisis Residential, Inpatient -- Innovative Programming in Chemical Dependency -- Innovative International Community Behavioral Health Models -- Criminal Justice: Diversion and Incarceration -- Homelessness -- Children and Youth -- Elders -- Rural Psychiatry -- Disaster Response -- Creating a Welcoming Service Environment -- Systems Transformation / engineering -- The Role of the Medical Director -- Program Evaluation -- How to be Successful in Research in Clinical Settings -- Medical Students and Residency -- Community/Public Psychiatry Fellowships -- Mentoring -- Ethics.
Keywords: Philosophy (General).; Psychiatry; Applied psychology; Psychology; Community and Environmental Psychology; Psychiatry